2021
DOI: 10.3390/pathogens10020112
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Feeding Waste Milk Containing Antimicrobial Residues on Dairy Calf Health

Abstract: A number of studies have reported that there is a high prevalence of antimicrobial-resistant faecal bacteria excreted by dairy calves. Although faecal shedding is influenced by a variety of factors, such as the environment and calf age, feeding milk with antimicrobial residues contributes significantly to an increased prevalence of antimicrobial-resistant (AMR) bacteria, such as extended spectrum beta-lactamase (ESBL)-producing E. coli. As a follow-up to the European Food Safety Authority (EFSA) Scientific Opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…A study in France demonstrated that young calves (<7 weeks of age) on dairy farms were harbouring a variety of AMR bacteria in their intestinal microbiome [27]. In particular, this study demonstrated that the proportion of ESBL-producing E. coli as determined by selective media, fell slightly from 22% at 15 days of age to 19% at 7 weeks [27]; a trend which has been observed in many other studies of the intestinal flora of dairy calves [28][29][30][31]. While the feeding of waste milk containing antimicrobial residues to calves did not appear to have a statistically significant effect on the farms sampled in the current study, a number of other studies have shown that feeding such milk to calves leads to a transient increase in the presence of AMR bacteria in their faeces [31][32][33][34].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A study in France demonstrated that young calves (<7 weeks of age) on dairy farms were harbouring a variety of AMR bacteria in their intestinal microbiome [27]. In particular, this study demonstrated that the proportion of ESBL-producing E. coli as determined by selective media, fell slightly from 22% at 15 days of age to 19% at 7 weeks [27]; a trend which has been observed in many other studies of the intestinal flora of dairy calves [28][29][30][31]. While the feeding of waste milk containing antimicrobial residues to calves did not appear to have a statistically significant effect on the farms sampled in the current study, a number of other studies have shown that feeding such milk to calves leads to a transient increase in the presence of AMR bacteria in their faeces [31][32][33][34].…”
Section: Discussionsupporting
confidence: 59%
“…In particular, this study demonstrated that the proportion of ESBL-producing E. coli as determined by selective media, fell slightly from 22% at 15 days of age to 19% at 7 weeks [ 27 ]; a trend which has been observed in many other studies of the intestinal flora of dairy calves [ 28 , 29 , 30 , 31 ]. While the feeding of waste milk containing antimicrobial residues to calves did not appear to have a statistically significant effect on the farms sampled in the current study, a number of other studies have shown that feeding such milk to calves leads to a transient increase in the presence of AMR bacteria in their faeces [ 31 , 32 , 33 , 34 ]. It is important to note that, similar to a Canadian study investigating extended-spectrum cephalosporin-resistant E. coli in calf faeces [ 34 ], the survey of farm management practices in the current study only provided “herd level” information and did not confirm that the calves sampled here had actually received waste milk containing antimicrobial residues, only that it was a routine practice on that farm.…”
Section: Discussionmentioning
confidence: 55%
“…Future studies should consider a longitudinal approach allowing the analysis of microbiota dynamics over time on larger farms or a greater number of farms, as well as establishing the directionality of the relationships between ESBL-PE status and the fecal microbiome. Furthermore, future studies should delve more deeply into the effect of contaminants in feed that could potentially drive AMR, as well as compositional elements of feed which may alter the overall fecal microbiome [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in Switzerland, 47.3% of surveyed dairy producers also used this WMA disposal method ( 7 ). However, this practice has come under scrutiny, as it has been associated with the selection of antibiotic resistance (AR) in the calves' commensal microbial flora ( 8 , 9 ). On the other hand, the disposal of WMA with manure or directly on the fields may also contribute to the persistence and spread of AR genes into the farm environment ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%